If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -2 = -5x + -3 Reorder the terms: -2 + -6x = -5x + -3 Reorder the terms: -2 + -6x = -3 + -5x Solving -2 + -6x = -3 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -2 + -6x + 5x = -3 + -5x + 5x Combine like terms: -6x + 5x = -1x -2 + -1x = -3 + -5x + 5x Combine like terms: -5x + 5x = 0 -2 + -1x = -3 + 0 -2 + -1x = -3 Add '2' to each side of the equation. -2 + 2 + -1x = -3 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = -3 + 2 -1x = -3 + 2 Combine like terms: -3 + 2 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1
| s^2-25b^2= | | 5d=1.33rt | | g^4-1= | | p=-3x+4y | | 6.9*x=69 | | 9x+14x=50 | | 5u^2-18u+9= | | 13x^2=52 | | (90y)-2y=5y-36 | | -7n=-n-14 | | 37-3x=1 | | 3h^2+5h-12= | | 5x+8=x+40 | | 3x+8=2x-6 | | W(w+10)=144 | | 4t^2-9t+5= | | 2x+5*sqrt(x)-3=0 | | 3(x+3y)-(2x+4y)=0 | | 5n+3n-n+s=26 | | 4x+x+2x=35 | | -12+12x=36 | | -8x+4y=80b | | 4z^2+z-5=0 | | -6(3f-8)=174 | | 6+3n=30 | | 18=-2x+4(x+8) | | x*20=1300 | | 70+(x+10)=(3x-22) | | X^2-65X+1000=0 | | F(x)=3x+8 | | 12e^2+17e+6= | | X^2+65x-1000=0 |